PEMANFAATAN ALOKASI DANA DESA TERHADAP PEMBANGUNAN PERDESAAN (STUDI KASUS DI TUNTANG KECAMATAN TUNTANG KABUPATEN SEMARANG) - Muhammad Safril Alam S; Arina Ulwiya; Maratu Nurhidayah (EP FEB UNS, 2018)
This study aims to determine the extent of the use of village fund allocations, to find out which results from the utilization of village fund allocations, and to find out community involvement in the utilization of village fund allocations. The method used in this study is descriptive qualitative with analytical techniques in the form of observation, interviews and collection of documents, the interviewees were people who were related to management and beneficiaries of the village fund allocation. Based on the results of the research and discussion that has been conducted, it is concluded that the people of Tuntang village received positively with the village funds. The allocation of village funds is beneficial for the village of Tuntang where the allocation of village funds contributes to the construction of infrastructure and social infrastructure such as schools and health facilities in the village of Tuntang. Keywords: Village Fund AllocationJEL Classification:H72